Cathepsin G Controls Arterial But Not Venular Myeloid Cell Recruitment. Issue 16 (18th October 2016) - Ortega-Gomez, Almudena; Salvermoser, Melanie; Rossaint, Jan; Pick, Robert; Brauner, Janine; Lemnitzer, Patricia; Tilgner, Jessica; de Jong, Renske J.; Megens, Remco T. A.; Jamasbi, Janina; Döring, Yvonne; Pham, Christine T.; et al.
Abstract : Background: Therapeutic targeting of arterial leukocyte recruitment in the context of atherosclerosis has been disappointing in clinical studies. Reasons for such failures include the lack of knowledge of arterial-specific recruitment patterns. Here we establish the importance of the cathepsin G (CatG) in the context of arterial myeloid cell recruitment. Methods: Intravital microscopy of the carotid artery, the jugular vein, and cremasteric arterioles and venules in Apoe –/– and CatG-deficient mice ( Apoe –/– Ctsg –/– ) was used to study site-specific myeloid cell behavior after high-fat diet feeding or tumor necrosis factor stimulation. Atherosclerosis development was assessed in aortic root sections after 4 weeks of high-fat diet, whereas lung inflammation was assessed after inhalation of lipopolysaccharide. Endothelial deposition of CatG and CCL5 was quantified in whole-mount preparations using 2-photon and confocal microscopy. Results: Our observations elucidated a crucial role for CatG during arterial leukocyte adhesion, an effect not found during venular adhesion. Consequently, CatG deficiency attenuates atherosclerosis but not acute lung inflammation. Mechanistically, CatG is immobilized on arterial endothelium where it activates leukocytes to firmly adhere engaging integrin clustering, a process of crucial importance to achieve effective adherence under high-shear flow. Therapeutic neutralization of CatG specifically abrogated arterial leukocyte adhesion without affecting myeloid cell adhesion in the microcirculation. Repetitive application of CatG-neutralizing antibodies permitted inhibition of atherogenesis in mice. Conclusions: Taken together, these findings present evidence of an arterial-specific recruitment pattern centered on CatG-instructed adhesion strengthening. The inhibition of this process could provide a novel strategy for treatment of arterial inflammation with limited side effects. Abstract : Supplemental Digital Content is available in the text.